Bottom-up on-crystal in-chip formation of a conducting salt and a view of its restructuring: from organic insulator to conducting "switch" through microfluidic manipulation1. Issue 6 (18th June 2015) - Puigmartí-Luis, Josep; Paradinas, Markos; Bailo, Elena; Rodriguez-Trujillo, Romen; Pfattner, Raphael; Ocal, Carmen; Amabilino, David B.
<x xml:space="preserve">Abstract</x> The chemical modification of an immobilized single crystal in a fluid cell is reported, whereby a material with switching functions is generated with reagent in the stream.